Foreign direct investment, globalized agri-food value chains and transformation - Saroj, Sunil; Veeramani, Choorikkad; Roy, Devesh; Kamar, Abul; Pradhan, Mamata (International Food Policy Research Institute, 2024)
We examine the determinants of participation and positioning in the Agriculture Globalized Value Chains (AGVC) with focus on role of foreign Direct Investment (FDI) in agriculture. Among the determinants, trade policies that are reflected in cost to trade play a significant role in AGVC engagement. FDI in agriculture affects AGVC structure correlating significantly with forward participation. FDI holds potential for enhancing value addition, technology diffusion, and market access. We then assess the effect of AGVC on production diversification in agriculture i.e., manifested in crop choices. A priori is unclear whether AGVC participation and positioning leads to greater specialization or diversification as there are forces in either direction. Our findings show that AGVC participation is associated with diversified agriculture. Moreover, the effect varies by positioning (backward and forward). The estimates using panel regression, Lewbel instrumental variable method and continuous treatment matching yielding dose response functions show these results to be robust. Results also vary regionally. East and Southeast Asia show the strongest association between AGVC and product diversification.